Smart Parcel Receiver Box - Abu Zarin, Nursyafieqa; Siti Zaharah Kunchi Mon, (Progress in Engineering Application and Technology, 2024)
The Smart Parcel Receiver Box, implemented at the UTHM Pagoh Residential College, addresses issues prevalent in traditional parcel storage. Before its creation, packages were left in paper boxes, leading to risks such as theft, damage, exposure to weather, and difficulties in location. Recipients had to wait for couriers to avoid these issues. The smart parcel box prototype emerged as a solution, ensuring secure storage through features like QR code scanning for recipient verification. Real-time database updates prevent unauthorized access, complemented by a user-friendly website for easy monitoring. This comprehensive solution not only enhances security but also streamlines the parcel management process, significantly improving the overall user experience at UTHM Pagoh Residential College.